Facile assembly of three cycloalkyne-modules onto a platform compound bearing thiophene S, S-dioxide moiety and two azido groups. Issue 34 (26th March 2020) - Meguro, Tomohiro; Sakata, Yuki; Morita, Takamoto; Hosoya, Takamitsu; Yoshida, Suguru
Abstract : An efficient method to assemble three cycloalkyne-modules onto a platform bearing a thiophene S, S -dioxide moiety and two azido groups has been developed. The sequential reactions without catalysis or additives enabled the facile preparation of trifunctional molecules by a simple procedure. Abstract : An efficient method to assemble three cycloalkyne-modules onto a platform compound bearing a thiophene S, S -dioxide moiety and two azido groups has been developed. The sequential reactions without catalysis or additives enabled the facile preparation of trifunctional molecules by a simple procedure. One-pot assembly was also achieved using the platform and three cycloalkynes.